Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Find the points on the curve $x^3 + y^3 = 2xy$ where the line tangent to the curve will be horizontal

I know that that this means that the derivative of the curve will be equal to 0. This is what I get: $$\frac{(2Y-3X^2)}{(3Y^2-X)} = 0$$ ..and then I'm stuck. Please help.

share|improve this question
Just to add a clarification to lab bhattacharjee's answer, a fraction is equal to 0 when the numerator is equal to 0. So you get $2Y-3X^2=0$ and then ultimately $2Y=3X^2$ (the first line of his answer). –  Conan Wong Dec 13 '12 at 16:29
that's clear....but what would be the point (s)?, the prof. hinted that the point(s) on the curve most satisfy the equation for the curve x3+y3=2xy –  carolina nunez Dec 13 '12 at 16:59
Keep in mind that this curve is not the graph of a function: some values of $x$ produce more than one value of $y$. The point $(0,0)$ is on the curve, but makes both the numerator and the denominator in the derivative of the implicit function equal zero. [Hint: on such a curve, sometimes a point can have two slopes!] –  RecklessReckoner Apr 28 '13 at 6:25
add comment

1 Answer

So, $2Y=3X^2$

Putting the value of $Y$ in the given equation, $$X^3(27X^3-16)=0\implies X=0,$$ or $X^3=\frac{27}{16}$

But, $X=0\implies Y=0,$ from $2Y=3X^2$

$ \frac{2Y-3X^2}{3Y^2-X}$ will be $\frac00$ hence undefined.

So, $X\ne0$

$X^3=\frac{27}{16}\implies \frac{3Y^2}X=\frac{3\left(\frac{3X^2}2\right)^2}X=\frac{27}4\cdot X^3$ (as $x\ne0$)

$\implies \frac{3Y^2}X=\frac{27}4\cdot \frac{27}{16}\ne1\implies 3Y^2-X\ne0$

So, $ \frac{2Y-3X^2}{3Y^2-X}$ will be $0$ as $2Y=3X^2$ but $3Y^2-X\ne0$

share|improve this answer
the points have to satisfy the equation of the curve.....i understand what you did, just don't know how to related it to the question –  carolina nunez Dec 13 '12 at 16:44
You have $2y=3x^2$. The curve is $x^3+y^3=2xy$. Multiply by $8$ to get $8x^3+(2y)^3=8x(2y)$. Use $2y=3x^2$ to rewrite this as $8x^3+27x^6=24x^3$. Can you take it from there? –  Gerry Myerson Dec 14 '12 at 0:24
But beware: x = 0 also solves that last equation, but does not seem to work in the derivative equation. There is something "funny" going on at the origin -- you'll need to check the curve to see why. –  RecklessReckoner Apr 28 '13 at 1:13
@RecklessReckoner, thanks for input. The values of $X$ deserves validation. –  lab bhattacharjee Apr 28 '13 at 6:08
add comment

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.